Analysis of attacking styles and goal-scoring in the 2021/22 Women’s Super League - Lizzie Craven; Patrick Oxenham; Jayamini Ranaweera (PLoS ONE, 2025)
The rapid rise in elite women’s football has increased the demand for female specific research to enable more accurate and appropriate assessments of tactical performance. Thereby, this study aimed to describe goal scoring in relation to different attacking styles during a Women’s Super League (WSL) season. Specifically, 1179 attacking sequences leading to shots on target performed by all 12 teams in the 2021/22 WSL season were analysed. The style of attack for each attacking sequence was characterised by research guided key performance indicators and recorded with the outcome of the subsequent shot on target. Descriptive results indicated that most shots (27.23%) were originating from combinative organised attacks, while set plays accounted for the most goals (27.08%), with fast organised attacks demonstrating the best goal conversation rates (53.33%). Outcomes of a chi-square test highlighted a significant (but weak) association between attacking styles and shot outcomes (χ42 = 9.87, P = 0.043) in the considered WSL season, with shots originating from set plays resulting in significantly more goals than expected (AR = 2.45). Overall, the results can be useful for practitioners when formulating tactical game plans and training sessions, while also providing multiple opportunities for future research in tactical analysis of women’s football.